1991
DOI: 10.1073/pnas.88.15.6863
|View full text |Cite
|
Sign up to set email alerts
|

Pyridinone derivatives: specific human immunodeficiency virus type 1 reverse transcriptase inhibitors with antiviral activity.

Abstract: Derivatives of pyridinones were found to inhibit human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) activity and prevent the spread of HIV-1 infection in cell culture without an appreciable effect on other retroviral or cellular polymerases. 3-{[(4,7-Dimethyl-1,3-benzoxazol-2-yl)methyljamino}-5-ethyl-6methylpyridin-2(LH)-one (L-697,639) and 3-{[(4,7-dichloro-1,3-benzoxazol-2-yl)methylJamino}-5-ethyl--methylpyridin-2(IH)-one (L-697,661) Infection with the human immunodeficiency virus type 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
167
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(175 citation statements)
references
References 22 publications
(11 reference statements)
8
167
0
Order By: Relevance
“…In previous studies it was found that TIBO and TIBOlike compounds inhibit HIV-1 RT non-competitively with respect to the natural substrate (Debyser et al, 1991;Goldman et al, 1991;Merluzzi et al, 1991). However, for HEPT itself, which is a relatively weak inhibitor of HIV-1 RT, we found a competitive type of inhibition (Debyser et al, 1992a).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous studies it was found that TIBO and TIBOlike compounds inhibit HIV-1 RT non-competitively with respect to the natural substrate (Debyser et al, 1991;Goldman et al, 1991;Merluzzi et al, 1991). However, for HEPT itself, which is a relatively weak inhibitor of HIV-1 RT, we found a competitive type of inhibition (Debyser et al, 1992a).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the classical RT inhibitors such as phosphonoformic acid (PFA) and 3'-azido-3'-deoxythymidine (AZT) 5'-triphosphate, TIBO and HEPT inhibit HIV-1 RT, but not HIV-2 RT. The more recently developed dipyridodiazepinones, pyridinones and bis(hetero-aryl)piperazines share this property (Merluzzi et al, 1990;Goldman et al, 1991;Romero et al, 1991). The HIV-l-specific RT inhibitors are ineffective not only against HIV-2 RT, but also against the RTs of avian myeloblastosis virus, Moloney murine leukaemia virus, SIV [from macaques (SlVmac)] and feline leukaemia virus (Merluzzi et al, 1990;Debyser et al, 1991;Goldman et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] Recently quinazolinones have gained recognition as they exhibit anti-HIV activity. 6-Chloro-(4S)-cyclopropyl-3,4-dihydro-4(2-pyridyl)ethynylquinazolin-2(1H)-one 1, a novel structural class of non-nucleoside inhibitors of HIV-1 reverse transcriptase (RT), displays synergistic inhibition of RT activity with AZT triphosphate.…”
Section: Introductionmentioning
confidence: 99%
“…They include tetrahydroimidazo-[4,5,Ijk] [1,4]benzodiazepin-2(1H)-one and -thione (TIBO) (4), nevirapine (8), 1-[(2-hydroxyethoxy)methyl]-6-(phenylthio)thymine (HEPT) derivatives (9), ot-anilinophenylacetamide (t~-APA) derivatives (5), and pyridinone derivatives (10). All of these compounds are highly inhibitory to HIV-I RT but are totally inactive against other retroviral RTs, including HIV-2, or cellular DNA polymerases (4,10). We have recently found 4-(2,6-dichlorophenyl)-l,2,5-thiadiazol-3-yl N,N-dialkylcarbamate (TDA) derivatives to be a novel class of HIV-1 inhibitors (11).…”
Section: Introductionmentioning
confidence: 99%